Immune function in Swedish elite orienteers - Lannergard, A.; Fohlman, J.; Wesslen, L.; Rolf, C.; Friman, G. (Scandinavian Journal of Medicine & Science in Sports, 2001)
During 1979-1992 an increased frequency of sudden unexpected cardiac death (SUD) occurred among young male Swedish elite orienteers. Subacute-to-chronic myocarditis was found in 12/16 (75%) at autopsy and Chlamydia pneumoniae, or a cross-reacting agent, was suspected on the basis of diagnostic tests performed. Because myocarditis is an infrequent cause of SUD and clusters of SUD are rare, whereas Chlamydia pneumoniae infections are ubiquitous and seldom cause severe myocarditis, 119 top ranked elite orienteers (67 males and 52 females) and 36 highly trained male middle-distance runners and cross-country skiers, serving as controls, underwent immunologic screening in an effort to reveal possible immune dysfunction. Except for two orienteers and one runner/skier who showed genetic C3-deficiency or IgA-deficiency, the results showed no significant differences between the orienteers and controls with respect to immunoglobulin levels, complement activation, lymphocyte subsets, including activated T lymphocytes, and sIL-2r-alpha. IL-1beta, IL-6, TNF-alpha, and sCD8, tested in the orienteers only, were normal. However, IFN-gamma was significantly higher in controls than in orienteers, who showed normal levels, whereas the orienteers had increased sELAM-1 and sICAM-1 levels. Finally, sIL-2 receptor-alpha was similarly elevated in orienteers and controls. We conclude that, with the tests employed, no immunologic disturbance could be revealed in the orienteers that may potentially have increased their susceptibility to myocarditis and SUD.